2018
DOI: 10.1016/j.alcr.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Gender and mathematics: Pathways to mathematically intensive fields of study in Australia

Abstract: Standards D and E of IPEd's Australian standards for editing practice, covering 'Language and illustrations' and 'Completeness and consistency'. Under these guidelines, matters of content were not edited, but were flagged for attention. The reference list was not included in the copy-edit. I take responsibility for any remaining errors of English grammar and appropriate style. The corrections and suggestions made by Elizabeth and Jon have always been useful for my thesis. Elizabeth and Jon not only corrected m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 145 publications
(292 reference statements)
2
7
0
Order By: Relevance
“…First, we found that gender differences in occupational expectations were the largest contributor to gender gaps in both fields, and explained 18.9% of the total gender gap (or 97.9% of the explained gender gap) in engineering-CTE enrollment, and 36.1% the total gender gap (or 86.8% of the explained gender gap) in health-CTE enrollment. This finding supports prior research that has found occupational expectations to be the largest contributor to gender gaps in 12th grade science coursetaking among students in Australia (Sikora, 2019) and extends the current base of research that has almost exclusively focused on the role of occupational expectations in contributing to gender gaps in STEMM fields at the postsecondary and career levels (Law, 2018;Legewie & DiPrete, 2014;Morgan et al, 2013;Sassler et al, 2017). While our results suggest that career aspirations were the largest contributor to gender gaps in both fields, holding counter-stereotypical beliefs regarding occupational expectations (i.e., females' expectations of entering engineering) was significantly associated with enrollment in nontraditional STEMM-CTE courses for both genders.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…First, we found that gender differences in occupational expectations were the largest contributor to gender gaps in both fields, and explained 18.9% of the total gender gap (or 97.9% of the explained gender gap) in engineering-CTE enrollment, and 36.1% the total gender gap (or 86.8% of the explained gender gap) in health-CTE enrollment. This finding supports prior research that has found occupational expectations to be the largest contributor to gender gaps in 12th grade science coursetaking among students in Australia (Sikora, 2019) and extends the current base of research that has almost exclusively focused on the role of occupational expectations in contributing to gender gaps in STEMM fields at the postsecondary and career levels (Law, 2018;Legewie & DiPrete, 2014;Morgan et al, 2013;Sassler et al, 2017). While our results suggest that career aspirations were the largest contributor to gender gaps in both fields, holding counter-stereotypical beliefs regarding occupational expectations (i.e., females' expectations of entering engineering) was significantly associated with enrollment in nontraditional STEMM-CTE courses for both genders.…”
Section: Discussionsupporting
confidence: 88%
“…As it relates to gender equity in STEMM, the most recent reauthorizations of Perkins (in 2006 and2018) include two particular calls to action: (1) equalizing access to CTE for underrepresented populations, including females, and (2) increasing STEMM coursetaking through the expansion of STEMM-CTE course offerings (also known as "applied STEM-CTE"). STEMM-CTE courses focus on applying math and science skills in more relevant ways and fall into 3 of the 16 broad CTE clusters: engineering technology, information technology, and health sciences (Bradby & Hudson, 2007).…”
mentioning
confidence: 99%
“…There are many phenomena tied with gender-related stereotypes in daily life, such as gender stereotypes reflected in the aspects of academic setting (Law, 2018;Muntoni and Retelsdorf, 2018) or career development (Heilman, 2012;Cadaret et al, 2017). For example, boys are believed to be outstanding in mathematics but weak in language learning, whereas girls are believed to be exactly the opposite and are consequently constrained in the choice and progress of math-related work.…”
Section: Gender-emotion Stereotypementioning
confidence: 99%
“…The stratification theory of gender essentialism argues that young people's selections of fields of study and occupations are strongly affected by persistent gender-essentialist beliefs and increasing self-expressive values (Cech, 2013;Charles & Bradley, 2009). Prior research has shown that boys and girls with gender-typical aspirations have a higher chance of selecting gender-typical disciplines in post-secondary education (Law, 2018;Morgan et al, 2013) and are more likely to end up in gender-typical occupations as adults (Polavieja & Platt, 2014). Studies seeking to explain the drivers of the gender wage gap and in particular why gender segregation in educational disciplines contributes so much to this gap have pointed to the importance of gender differences in occupational and earnings aspirations (Gerber & Cheung, 2008;Ochsenfeld, 2014).…”
Section: Introductionmentioning
confidence: 99%